Children and Students with Disabilities Are Beneficiaries from the Parental and Teacher Participation - Zulkipli Lessy; Nur Hamzah; Thalita Hayu Maharsani (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
Community-based therapeutic healing, then abbreviated C-bTH, has crucial advantages for parents, teachers, and their students with disabilities to partcipate in reciprocal help that facilitates social participation to avoid self-alienation. This study examines the social participation of the parents and the shadow teachers for their children and students with disabilities for fulfilling their needs. The sampling includes 15 adults together with three administrative officers who were involved in the C-bTH. To gather data, in-depth interviews and observations were employed. The data were analyzed via the phenomenological approach that perceives data as what it shows itself as it is without the researcher imposed his/her thoughts on it. The study revealed four themes connected to basic needs of children and students with disabilities to be fulfilled. Results showed the engagement of the parents in the C-bTH and the teacher at school all of which is to meet the basic rights of the children with disabilities. First, the parents accompany their children to participate in the therapeutic healing. They have helped the children to develop physically and psychologically. Second, the parents and the teachers involved in Islamic education such as teaching, learning, and evaluation. Third, the parents participated in the entrepreneurial and cooperative programs to support the children and to evaluate the services. Fourth, the parents participated in recreation and shared their experience.